Sistem Pendukung Keputusan Menentukan Siswa Penerima Beasiswa Di SMKS Patriot Nusantara Jakarta Dengan Metode Analytical Hierarchy Process Berbasis Java Desktop - Salna Tilawati; Irwan Agus; Adhityo Kuncoro (Jurnal Cakrawala Informasi, 2023)
Patriot Nusantara Private Vocational High School (SMKS) is an educational institution in Jakarta, Patriot Nusantara SMKS organizes educational assistance programs through scholarships. There are various types of scholarships given, namely scholarships given to underprivileged and high achieving students. The Student Study Assistance Scholarship (BBS) is a type of scholarship for economically disadvantaged students, while the Academic Achievement Improvement Scholarship (PPA) is a scholarship given to high-achieving students. To find patterns in determining scholarship recipients, a decision support system was built, through research. This research uses the Analytical Hierarchy Process (AHP) method. This method is used to evaluate and make multi-criteria decisions. It evaluates various alternatives based on different criteria and assigns a relative score to each alternative. Based on the results of this research, it produces better and more accurate calculations. If previously selection took 10 hours, now with the decision support system the selection time is shorter.